MENINGKATKAN HASIL BELAJAR BIOLOGI MELALUI MODEL PEMBELAJARAN MAKE A MATCH PADA SISWA SMP - Mudrikah Mudrikah (Cendekia: Jurnal Pendidikan dan Pembelajaran, 2016)
The objective of this study is to increase achievement on biology subject using learning model make a match.  This study used classroom action research design with three cycles.  The study took place in SMPN 1 Karangploso Malang involving 32 students as subject.  Instruments of this study were obsevation sheets and questionnaire.  Data of the study were learning process the students involved in the make a match instructions.  Data were analyzed using descriptive statistics to draw students minimum score achievement and rate percentage in every cycle.  The study revealed: (1) rate percentage of mastery learning in cycle I is 63.2%, cycle II 72% and cycle III 86.9% respectively and (2) students’ mastery of achievement in cycle I is 7 (21.8%) finished and 25 (78.1%) unfinished, in cycle II: 19 (59.4%) finished and 13 (40.6%) unfinished; in cycle III:  28 (87.5%) finished and 4 (12.5%) unfinished.